Synthesis and preliminary anticancer activity of new 1H-4,5-dihydro-3-(3- hydroxy-2-naphthyl)-4-substituted-1,2,4-triazoline-5-thiones. Part II - (:unkn) unknown (My University, 2005)
The compounds 1H-4,5-dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-1,2,4- triazoline-5-thiones have been synthesised from 3-hydroxy-2-naphthoic acid hydrazide in two steps. The structural elucidation of the synthesised compounds has been performed by 1H NMR and mass spectroscopic data besides elemental analyses. Some of the compounds are tested in vitro for their ability to inhibit growth of 60 different human cancer cell lines by the National Cancer Institute and notable cytotoxic effect on some cancer cell lines is observed from some of them as expected in comparison with the control agent 5-fluorouracil.
Keywords: 1H-4,5-dihydro-3-(3-hydroxy-2-naphthyl)-4-substituted-1,2, 4-triazoline-5-thiones; Anticancer activity